The Origins of Staphylococcus aureus Isolated from Blepharitis Based on Panton-Valentine Leukocidin and Antibiotic Susceptibility Testing - Elam, Angela R.; Kowalski, Tyler A.; Romanowski, Eric G.; Kowalski, Regis P. (Journal of Ocular Diseases and Therapeutics, 2014)
Introduction: Blepharitis is a common condition, sometimes associated with Staphylococcus aureus. Panton-Valentine Leukocidin (PVL) toxin is a Staphylococcus aureus virulence factor that can be associated with skin and soft tissue infections. Hospital-acquired Staphylococcus aureus infections are generally multi-resistant to antibiotics and PVL-negative. Community-acquired Staphylococcus aureus infections tend to be broadly susceptible to antibiotics and PVL-positive. Though blepharitis is a common clinical diagnosis, the source of infection is not fully understood. Focus on the origin of disease could aid in better treatment and reduction of anti-infective resistance. The purpose of this study is to determine if Staphylococcus aureus blepharitis is predominantly a community-acquired or hospital-acquired infection based on antibiotic susceptibility and PVL testing. Materials and Methods: Fifty-nine de-identified Staphylococcus aureus isolates collected from patients with blepharitis were tested for antibiotic susceptibility by disk diffusion using multiple antibiotics from several different classes. The isolates were also tested for the presence of Staphylococcus aureus nuclear DNA and PVL toxin gene using PCR. Multi-resistance was defined as resistance to 3 or more classes of antibiotics. Results: Of the 59 isolates with PCR-identified Staphylococcus aureus DNA, 13 (22%) were multi-resistant; 12 (20%) were methicillin-resistant; and, 3(5%) were PVL-positive. Ten (17%) were multi-resistant and PVL-negative, consistent with hospital-acquired infection. None of the isolates were broadly susceptible to antibiotics and PVL-positive, which would be consistent with community-acquired infection. Forty-nine isolates (83%) (p=0.0001) could not be designated to either group. Conclusion: Based on PVL and antibiotic susceptibility testing, our results reject the hypothesis that Staphylococcus aureus blepharitis is a community-acquired infection. Staphylococcus aureus blepharitis appears not to be predominantly community- or hospital-acquired based on these parameters.